Run on your new legs. 1 - Midori, Wataru (Yen Press, 2022)
"Shouta Kikuzato's hopes of starting on his school's prestigious soccer team are derailed when a terrible incident costs him his leg. Now in his first year of high school (again), Kikuzato has resigned himself to never reaching his athletic dreams. But when Chidori, a passing prosthetist, notices Kikuzato's artificial limb-- and speed--as he races through the train station, the specialist proposes a partnership: Chidori will build Kikuzato a brand-new leg designed solely for speed. All Kikuzato has to do is run!"--provided by publisher.